Special summation 2

Algebra Level 3

1 1 3 2 3 + 1 2 3 3 3 + 1 3 3 4 3 + = A π B + C \dfrac{1}{1^32^3}+\dfrac{1}{2^33^3}+\dfrac{1}{3^34^3}+\cdots=A\pi^B+C

The equation above holds true for rational numbers A A , B B , and C C . Find A + B + C A+B+C .

Reference question:

Special summation 1

Special summation 3


The answer is 11.000.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

The sum = n = 1 1 n 3 ( n + 1 ) 3 = n = 1 [ 1 n ( n + 1 ) ] 3 = n = 1 ( 1 n 1 n + 1 ) 3 = n = 1 [ 1 n 3 3 n 2 ( n + 1 ) + 3 n ( n + 1 ) 2 1 ( n + 1 ) 3 ] = n = 1 [ 1 n 3 1 ( n + 1 ) 3 ] 3 n = 1 1 n 2 ( n + 1 ) 2 = 1 3 ( π 2 3 3 ) = 10 π 2 A + B + C = 1 + 2 + 10 = 11.000 \quad \text{The sum} \\= \displaystyle\sum_{n=1}^\infty \dfrac{1}{n^3(n+1)^3} \\= \displaystyle\sum_{n=1}^\infty \left[\dfrac{1}{n(n+1)}\right]^3 \\= \displaystyle\sum_{n=1}^\infty \left(\dfrac{1}{n}-\dfrac{1}{n+1}\right)^3 \\= \displaystyle\sum_{n=1}^\infty \left[\dfrac{1}{n^3}-\dfrac{3}{n^2(n+1)}+\dfrac{3}{n(n+1)^2}-\dfrac{1}{(n+1)^3}\right] \\= \displaystyle\sum_{n=1}^\infty \left[\dfrac{1}{n^3}-\dfrac{1}{(n+1)^3}\right] -3\displaystyle\sum_{n=1}^\infty \dfrac{1}{n^2(n+1)^2} \\= 1-3\left(\dfrac{\pi^2}{3}-3\right) \\= 10-\pi^2 \\ \therefore A+B+C=-1+2+10=\boxed{11.000}

*In the fifth step, I use the answer in Special summation 1 .

S = n = 1 1 n 3 ( n + 1 ) 3 By partial fraction decomposition = n = 1 ( 6 n 2 3 n + 1 n 3 6 n 2 + 15 n + 10 ( n + 1 ) 3 ) = n = 1 ( 6 n 3 n 2 + 1 n 3 6 n + 1 3 ( n + 1 ) 2 1 ( n + 1 ) 3 ) = 6 n = 1 ( 1 n 1 n + 1 ) 6 n = 1 1 n 2 + 3 ( 1 1 2 ) + n = 1 ( 1 n 3 1 ( n + 1 ) 3 ) Riemann zeta function ζ ( s ) = k = 1 1 k s = 6 6 ζ ( 2 ) + 3 + 1 = 10 π 2 and ζ ( 2 ) = π 2 6 \begin{aligned} S & = \sum_{n=1}^\infty \frac 1{n^3(n+1)^3} & \small \blue{\text{By partial fraction decomposition}} \\ & = \sum_{n=1}^\infty \left(\frac {6n^2-3n+1}{n^3} - \frac {6n^2+15n+10}{(n+1)^3}\right) \\ & = \sum_{n=1}^\infty \left(\frac 6n - \frac 3{n^2} + \frac 1{n^3} - \frac 6{n+1} - \frac 3{(n+1)^2} - \frac 1{(n+1)^3} \right) \\ & = 6 \sum_{n=1}^\infty \left(\frac 1n - \frac 1{n+1}\right) - 6 \blue{\sum_{n=1}^\infty \frac 1{n^2}} + 3\left(\frac 1{1^2}\right) + \sum_{n=1}^\infty \left(\frac 1{n^3} - \frac 1{(n+1)^3}\right) & \small \blue{\text{Riemann zeta function }\zeta (s) = \sum_{k=1}^\infty \frac 1{k^s}} \\ & = 6 - 6 \blue{\zeta (2)} + 3 + 1 = 10 - \pi^2 & \small \blue{\text{and }\zeta (2) = \frac {\pi^2}6} \end{aligned}

Therefore, A + B + C = 1 + 2 + 10 = 11.000 A+B+C = - 1 + 2 + 10 = \boxed{11.000} .


Reference:

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...